Improving Graduate Competence Through Integration of Business English and Soft Skills - Rudiyanto, Mohammad; Syaiful, Syaiful; Ria Kasanova (CV. ULIL ALBAB CORP, 2025)
This article discusses the importance of integrating Business English and soft skills in improving the competence of graduates at the Faculty of Teacher Training and Education (FKIP) Universitas Madura. By adopting a qualitative approach, this study revealed the perceptions of students and graduates regarding the relevance of these two skills in the world of work. The results show that graduates who participated in this integrated program are more confident and able to communicate effectively, both in English and interpersonal contexts. However, challenges remain in implementing this program, including limited resources and relevant teaching materials. Therefore, it is recommended that FETT Universitas Madura design a more comprehensive training program for lecturers and periodically update the curriculum in line with industry developments. This research also shows that mastery of English and soft skills not only increases the competitiveness of graduates in the job market but also contributes to the professionalism and effectiveness of teaching in the educational environment. The integration of these two skills is expected to be a model for other educational institutions to prepare competent educators who are ready to face challenges in the global era.